Potassium-magnesium imbalance causes detrimental effects on growth, starch allocation and Rubisco activity in sugarcane plants - Garcia, Ariani [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Rosolem, Ciro Antonio [UNESP]; Bossolani, João William [UNESP]; Nascimento, Carlos Antonio Costa; McCray, James Mabry; dos Reis, André Rodrigues [UNESP]; Cakmak, Ismail (Springer Nature, 2022)
Background and aims: While there is abundant literature on the antagonistic interaction between potassium (K) and magnesium (Mg) during root uptake and transport, there is, however, little published data on the interaction between these nutrients within tissue, especially for sugarcane plants having high demand for K and Mg. This study aimed to investigate the effects of the interactions between K and Mg. Methods: Plants were grown in nutrient solution with increasing K application doses at low and adequate Mg treatments under controlled greenhouse conditions. Leaves, stalks and roots have been analyzed for growth, nutrient concentrations, starch partitioning, and activity of Rubisco. Results: There were significant decreases in Mg concentration in all plant parts by increasing K supply, especially in roots. Leaf symptoms of Mg deficiency appeared not only in low Mg, but also in Mg adequate plants when plants treated with very high K. Magnesium adequate plants contained much higher amount of starch in roots, stalks and young leaves than the low Mg plants when K applications were at low levels. By contrast, there was a high accumulation of starch in the older leaves of the Mg deficient plants. Magnesium deficiency was also associated with significant decreases in Rubisco activity in leaves. Conclusion: Our results show clearly that high K doses interfere significantly with the positive effects of Mg on plant growth, Rubisco activity and starch accumulation in sink organs such as roots and stalks. It is obvious that the imbalance between K and Mg nutrition in sugarcane results in adverse consequences in sugar yield capacity.
Keywords: Magnesium and Rubisco; Potassium; Saccharum spp; Shoot and root growth; Starch allocation; Sugarcane